Age‐Related Changes in Speed and Mechanism of Adult Skeletal Muscle Stem Cell Migration12. (15th May 2012) - Collins‐Hooper, Henry; Woolley, Thomas E.; Dyson, Louise; Patel, Anand; Potter, Paul; Baker, Ruth E.; Gaffney, Eamonn A.; Maini, Philip K.; Dash, Philip R.; Patel, Ketan
Abstract: Skeletal muscle undergoes a progressive age‐related loss in mass and function. Preservation of muscle mass depends in part on satellite cells, the resident stem cells of skeletal muscle. Reduced satellite cell function may contribute to the age‐associated decrease in muscle mass. Here, we focused on characterizing the effect of age on satellite cell migration. We report that aged satellite cells migrate at less than half the speed of young cells. In addition, aged cells show abnormal membrane extension and retraction characteristics required for amoeboid‐based cell migration. Aged satellite cells displayed low levels of integrin expression. By deploying a mathematical model approach to investigate mechanism of migration, we have found that young satellite cells move in a random "memoryless" manner, whereas old cells demonstrate superdiffusive tendencies. Most importantly, we show that nitric oxide, a key regulator of cell migration, reversed the loss in migration speed and reinstated the unbiased mechanism of movement in aged satellite cells. Finally, we found that although hepatocyte growth factor increased the rate of aged satellite cell movement, it did not restore the memoryless migration characteristics displayed in young cells. Our study shows that satellite cell migration, a key component of skeletal muscle regeneration, is compromised during aging. However, we propose clinically approved drugs could be used to overcome these detrimental changes. STEM CELLS 2012;30:1182–1195